2018
DOI: 10.1088/1361-6641/aaa611
|View full text |Cite
|
Sign up to set email alerts
|

The zinc-loss effect and mobility enhancement of DUV-patterned sol–gel IGZO thin-film transistors

Abstract: We investigate the composition of the DUV-patterned sol-gel indium gallium zinc oxide (IGZO) thin-film transistors (TFTs) and observe a significant zinc loss effect during developing when the DUV exposure is insufficient. The zinc loss, however, is beneficial for increasing the mobility. Reducing zinc to indium composition ratio from 0.5 to 0.02 can effectively increase mobility from 0.27 to 7.30 cm 2 V -1 s -1 when the gallium to indium ratio is fixed as 0.25 and the post annealing process is fixed as 300 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Along with the spectrum of the lamp, the efficiency of the photoinduced conversion depends on various additional parameters, one of which is the emitted power density. The levels of irradiance (optical power per unit area) reported in the literature are rather wide and spans from 0.8 mW cm −2 (lower end) up to 1 W cm −2 (higher end) . Many studies, however, used DUV lamps with irradiance values smaller than 60 mW cm −2 .…”
Section: Photochemical Conversion Of Metal‐oxide Precursors Via Deep mentioning
confidence: 99%
See 4 more Smart Citations
“…Along with the spectrum of the lamp, the efficiency of the photoinduced conversion depends on various additional parameters, one of which is the emitted power density. The levels of irradiance (optical power per unit area) reported in the literature are rather wide and spans from 0.8 mW cm −2 (lower end) up to 1 W cm −2 (higher end) . Many studies, however, used DUV lamps with irradiance values smaller than 60 mW cm −2 .…”
Section: Photochemical Conversion Of Metal‐oxide Precursors Via Deep mentioning
confidence: 99%
“…Furthermore, the application of DUV light can be carried out across a wide range of processing times depending on the application and the type of UV lamp employed. It has been shown that exposure for only 30 s is sufficient when used as a mean for patterning the metal‐oxide precursor, but increases to tens of minutes, or even several hours, when a complete chemical conversion is required . An overview of the electrical properties of selected DUV treated metal‐oxide TFTs can be found in Table 2 .…”
Section: Photochemical Conversion Of Metal‐oxide Precursors Via Deep mentioning
confidence: 99%
See 3 more Smart Citations